"Backstage Autonomy": Religious-Zionist State Widows in Second Marriages Manage Competing Expectations. (3rd July 2018) - Lebel, Udi; Luwisch-Omer, Shoshana; Possick, Chaya
ABSTRACT: The article examines the coping mechanisms of state widows belonging to Israel's Religious-Zionist sector, whose husbands died at an early age either during military service or in terrorist attacks. While the national bereaved community's collective unconscious expects the widows to dedicate their lives to institutionalized commemoration of their dead husband, Jewish tradition expects them to remarry to rehabilitate their family and children. The widows who were studied seemed to manage the competing expectations successfully: they remarried and maintained a happy family life while entrusting commemoration to the bereaved parents, who are still part of their extended family. The findings point to successful manipulation of the patriarchy of both communities to which they belong, achieving individualization that offers freedom in the private sphere—what we call "Backstage Autonomy"—while perpetuating hegemony on the public level on the Front Stage.